Phenology of Apple Worm Development in Climate Conditions of Boysun and Termiz Districts - Mardonayeva Dilsora Norkhonovna; Tokhtayeva Mukhlisa Bakhtiorovna; Abrayev Husniddin Nurmuhammad ogli (Scientific Trends, 2022)
This article provides information on the influence of the climatic conditions of Boysun and Termiz districts on the development of the apple worm, as well as the phenology of the development of the apple worm under different conditions, and the damage it causes.
Keywords: Apple worm, orchard, pest, caterpillar, egg, fungus, mature butterfly, phenology